Pengelolaan Yayasan Albanna sebagai Lembaga Pendidikan Islam di Denpasar Selatan 2007-2019 - Salsabila, Deanita (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 21 No 2 (2021)DO - 10.24843/PJIIB.2021.v21.i02.p07, 2021)
This research study discusses the Management of the Albanna Foundation for Islamic Education Institutions in South Denpasar 2007-2019. The purpose of this study is to find out the background of the formation of the Albanna Foundation, how the Albanna Foundation management system is and what challenges are faced by the Albanna Foundation managers. The research methodology used by the author is the social history of education. The theory used in the research by the author is called historical theory such as historical understanding and structural functional theory. The results of this study explain that the formation of the Albanna School started from the idea to pioneer an Islamic School from the Albanna builder and administrator founded by Saifuzzuhri. The Albanna Foundation is an Islamic school that has a religious character and has a global perspective in the concept of Islamic education that provides support for school efforts to advance themselves and implement a management system and infrastructure in Albanna. The challenges in managing the Albanna Foundation he faced with reference to technology and human resources.